Legal Prescriptions and the Effectiveness of Sanctions for Harassment and Malpractice in Traditional Medicine Clinics - Sirenden, Monita Tinting; Issalillah, Fayola; Vitrianingsih, Yeni (Journal of Social Science Studies, 2024)
This literature study examines the legal framework for protecting patients from harassment and malpractice in traditional medicine clinics in Indonesia, focusing on legal prescriptions and sanction mechanisms. The research employs a normative juridical method, analyzing primary and secondary legal sources. The findings indicate that patient protection is normatively regulated through a multi-layered framework encompassing administrative law (Government Regulation No. 103 of 2014 on Traditional Health Services), civil law (Civil Code and Consumer Protection Law), and criminal law (Criminal Code and Sexual Violence Crime Law). However, the effectiveness of these legal instruments is significantly constrained. Qualifying and proving malpractice elements within the unique context of diverse and less-standardized traditional practices poses a major challenge. Furthermore, the enforcement of administrative, civil, and criminal sanctions is hindered by weak inter-institutional coordination, limited supervisory capacity, substantial evidentiary barriers due to poor documentation, and profound socio-cultural obstacles such as stigma and community pressure. These factors collectively undermine the deterrent effect on perpetrators and the adequacy of remedies for victims. The study concludes that strengthening patient protection requires not only regulatory refinement but also systemic improvements in oversight implementation, law enforcement capacity, victim support systems, and public legal awareness.